2017
DOI: 10.1371/journal.pone.0178765
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1/PD-L2-expressing B-1 cells inhibit alloreactive T cells in mice

Abstract: B cells constitute a complex system of antigen-presenting cells (APCs) and exist as distinct subsets that differ in their lineage affiliation, surface molecule expression, and biological function, thus potentially regulating the immune response. In this study, we investigated the immune-regulatory roles of murine B cell subsets as regulatory APCs targeting alloreactive T cells. Either splenic B cells, peritoneal cavity (PerC) B cells, or non-B cells from Balb/c mice were intravenously injected into B6 mice. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…PD-L1 expression in splenic B cells was elevated during acute and chronic infection, whereas the expression of PD-L1 in PerC B cells was decreased during chronic schistosomiasis. The difference in PD-L1 expression of B cells during infection might be due to the higher basic level of PD-L1 in PerC B cells compared to that in splenic B cells [45] and the infection-induced migration of PerC B-1a cells to the liver [46].…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 expression in splenic B cells was elevated during acute and chronic infection, whereas the expression of PD-L1 in PerC B cells was decreased during chronic schistosomiasis. The difference in PD-L1 expression of B cells during infection might be due to the higher basic level of PD-L1 in PerC B cells compared to that in splenic B cells [45] and the infection-induced migration of PerC B-1a cells to the liver [46].…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive B cell subsets, which inhibit immune responses by production of Interleukin-10 (IL-10), Granzyme B or expression of PD-L1 have been described. [22][23][24][25] However, in our study regulatory B cell subsets (CD24 ++ CD38 ++ or CD24 high CD27 + in % of CD 19 + CD20 + ) were not increased in tumor samples (1.6% ± 0.3 and 10.1% ± 2.0) compared to TDLN (0.5% ± 0.1 and 5.3% ± 1.1, p = 0.4 and 0.1), PBMC of EAC patients (3.1% ± 0.5 and 18.5% ± 2.1, p < 0.05) and PBMC of healthy controls (3.1% ± 0.4 and 20.0% ± 2.2, p < 0.05 and 0.2; Supplementary Figure 3A, B). In addition, PD-L1 + B cells were not enriched in the tumor microenvironment (1.9% ± 0.4) compared to PBMC AC (1.8% ± 0.3, p = 1.0) and PBMC HC (1.0% ± 0.1, respectively, p = 0.9, Supplemetary Figure 3C).…”
Section: B Cell Infiltrates Are Decreased In Tumors Containing Factormentioning
confidence: 99%
“…Hirose et al. demonstrated that PD‐L1 and PD‐L2 expressed by peritoneal cavity B‐1a cells mediated a reduction in CD4 + and CD8 + T cells in mice through interaction with PD‐1, whereas blocking PD‐L1 and PD‐L2 led to an increase in CD4 + and CD8 + T cells …”
Section: Immunoregulatory Network Of Bregsmentioning
confidence: 99%
“…ligand (FasL),[48][49][50][51] TRAIL,52,53 and programmed death-ligand (PD-L) 1 and 2,[54][55][56][57][58] all of which can initiate the programmed cell death of target cells 39. The interaction of FasL, expressed by B cells, with the Fas receptor can initiate a signaling cascade that leads to Th cell apoptosis48,49 ;Th cell apoptosis induced by B cells was first directly demonstrated by using FasL + B cells to kill CD4 + T cells 50.…”
mentioning
confidence: 99%
See 1 more Smart Citation